Use of Learning Model Cooperative Learning Type Team Games Tournament (TGT) to Improve Interpersonal Intellegence of Students in Social Studies Learning. - Subandi, Andi (Universitas Pendidikan Indonesia, 2018)
The research was distributed by early observations in Class VII-5 Junior High School 1 Bandung. Observation results showed low interpersonal intelligence the learners that are happening in the learning process, problems that arise are: 1) the students who are less appreciative of other learners, 2) lack of healthy communication between learners, 3) lack of social sensitivity of the learners. To solve the problem of the study, researchers conducted a study class act with a design model Kemmis and McTaggart uses learning model cooperative learning-type team games tournament. This research was carried out through three cycles each cycle consisting of a single action. In the first Act, the study was conducted in two stages using intelligent game closely. The first Act shows the interpersonal intelligence in the category of